2019
DOI: 10.14434/josotl.v19i4.25747
|View full text |Cite
|
Sign up to set email alerts
|

Active Learning Strategies and Competency-Based Design in Research Education: a Longitudinal Review

Abstract: This paper describes the long-term re-development of an introductory graduate research methods course. The initial design is presented, followed by the two re-design phases. Phase 2 introduced additional inquiry-based strategies such as concept mapping and multiple levels of peer collaboration. Phase 3 incorporated competency-based techniques as well as additional technical, social, and instructional support. Assessment results, student feedback, moderate to strong relationships between scores on key assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Nguyen et al (2021) suggested to plan effective team-based activities and to encourage students to give feedback to others. Haughton (2019) encouraged within-group collaboration and then between-group collaboration to support a communicative and supportive classroom environment. This suggestion of providing collaborative opportunities also agrees with Johnson et al (2019), where researchers used an open-space learning activity to promote students’ collaborative and active learning when teaching mixed methods in health science.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nguyen et al (2021) suggested to plan effective team-based activities and to encourage students to give feedback to others. Haughton (2019) encouraged within-group collaboration and then between-group collaboration to support a communicative and supportive classroom environment. This suggestion of providing collaborative opportunities also agrees with Johnson et al (2019), where researchers used an open-space learning activity to promote students’ collaborative and active learning when teaching mixed methods in health science.…”
Section: Discussionmentioning
confidence: 99%
“…The collaboration opportunities are aligned with Nguyen et al’s (2021) planning strategies and Haughton’s (2019) multiple levels of peer collaboration strategies. Nguyen et al (2021) suggested to plan effective team-based activities and to encourage students to give feedback to others.…”
Section: Discussionmentioning
confidence: 99%
“…A good PBL exercise design should integrate the assessment of both hard and soft skills. 16 In addition, self-assessments also foster learning through motivation and promoting metacognition. 27,28 These assessment practices and data sources support all the five Engineering Technology ABET Criterion 3.…”
Section: Literature Reviewmentioning
confidence: 99%
“…13 The integration of other active learning strategies such as peer-assisted learning can also help to build foundational knowledge and bridge knowledge gaps. 8,[14][15][16]…”
Section: Project-based Learningmentioning
confidence: 99%
“…The National Institute for Learning Outcomes Assessment (NILOA) holds that learning assessment should be primarily directed at well‐developed course assignments. “When carefully structured, they elicit knowledge and behaviors that can be calibrated to the specific proficiencies individual instructors, programs, and institutions deem important” (Hutchings et al, 2014, p. 3; also see Haughton, 2019). In other words, assignments can be oriented toward developing the transferable leadership competencies students need in a given profession, even if the course subject is not leadership.…”
Section: Build For Transferable Skills: Design An Assignment To Develop Leadership Competencymentioning
confidence: 99%